A systematic approach to engagement and quality assurance in transnational education: an Australian university case study - Pedigo, Kerry; Soontiens, Werner (The Academy of World Business, Marketing, and Management Development, 2012)
In a TNE environment, induction and staff development is mostly done from afar, supported by occasional academic visits to offshore locations. Consequently, there can be a perceived lack of overall connectedness between home and partner campus understandings of quality assurance, academic alignment and policy implementation. In implementing a different multi-faceted approach to staff induction, the Curtin Business School (CBS) endeavoured to augment staff engagement, build inter and intra relationships between all staff, advance a common understanding of university policies and procedures, and assure quality teaching and learning practices. The following paper presents the processes, analysis and findings in facilitating an offshore staff induction program onshore. The results not only identified skill development and understanding but also a depth of commitment and connectedness much greater and deeper than that anticipated.